Multiple modalities of teaching civic education awareness among students: a pragmatic approach-based case study - Muhammad Younas; Muhammad Imran (Cogent Education)
This study aims to highlight the positive impact of civic education on young minds and addresses the challenges of liberal assurance and inefficacy in civic education as practiced in many societies. It seeks to determine the necessity of promoting civic education at a higher level to comprehend the beliefs and perspectives of young individuals. The research involved 25 undergraduate students from diverse academic backgrounds. Data was gathered through semi-structured interviews using multi-stage sampling techniques. Thematic analysis was employed to interpret the data, providing a comprehensive understanding of the participants’ views on civic education. The analysis revealed a spectrum of perspectives on civic education among the students. A significant positive relationship was identified between civic education awareness and its prevalence. The findings highlight that enhancing civic education awareness requires a collaborative effort involving not only the educational system but also the state and communities. This case study contributes to the discourse on civic education by demonstrating its critical role in shaping young minds. It underscores the collective responsibility of educational institutions, state authorities, and communities in fostering civic awareness. The study’s pragmatic approach provides valuable insights for policymakers and educators seeking to enhance civic education and engagement among youth.